Research of Reachable Workspace of 2-RPR+RRP Spherical Hybrid Mechanism - Zhao Jianwen; Song Shengtao; Li Ruiqin; Li Dahai (Jixie chuandong)
The reachable workspace of 2- RPR + RRP spherical hybrid mechanism is researched. Firstly,the degree of freedom of the mechanism is solved by the modified Kutzbach- Grvbler formula,the degree of freedom of the mechanism and the motion characteristics of moving platform are obtained. Secondly,taking the geometric relation of mechanism as the constraint condition and combining with the rotation matrix,the mathematical model of the closed positive solution of the kinematics position of the mechanism is established. Finally,according to the positive kinematics solution model,the Matlab software is used to draw up the workspace of the reference point in the specific condition,and the reachable workspace of the same conditions is verified by using the Solid Works simulation software. The correctness of the positive solution model is proved,a theoretical basis for the further analysis and optimization of the mechanism is provided.